Efficiency Improvement of Capacitor Operation - V. P. Kashcheev; E. O. Voronov; V. V. Akulshin; A. Y. Unukovich; O. V. Kashcheeva; V. N. Sorokin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A system of modernized capacitor ball-cleaning that prevents formation of depositions on internal capacitor tube surface has been developed in the paper.The system has been introduced at the Minsk TPP-4 (Power Block No.5). The paper presupposes that the economic effect will be nearly 0.43 million US dollars per year at one poer block with turbine Т-250/300-240.